TM600E: An ATCA-based 10-Gigabit Metro Ethernet Switch - Khyasudeen, MF; Ramli, MR; Daud, WN; Seman, K (IEEE, 2024)
Telecom Service Providers (TSPs) are facing big challenges in today's telecom markets due to the introduction of packet-based network. Users demand more on higher and flexible bandwidth together with high Quality of Set-vice (QoS). These problems require TSPs to seek new network technology that can meet such challenges. Metro Ethernet has been regarded as the technology of choice due to its universality, and high flexibility. This paper is about the design of Telekom Malaysia's TM600E that is a 10Gigabit switch to be used as the Edge Provider Edge (EPE) device in the Metro Ethernet Network. The Advanced Telecom Computing Architecture (ATCA) has been chosen for providing the open architecture platform. Performance testing conducted confirms that the switch has high throughput, low latency, and low packet loss.